2006
DOI: 10.1161/01.atv.0000194074.59584.42
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Activation by Tumor Necrosis Factor α Through Neutral Sphingomyelinase 2, Sphingosine Kinase 1, and Sphingosine 1 Phosphate Receptors

Abstract: Objective-Tumor necrosis factor ␣ (TNF-␣), a key proinflammatory cytokine acting on the endothelium, activates endothelial nitric oxide synthase (eNOS). We have examined the signaling pathway leading to this activation and its biological role in endothelium, which are still unknown. Methods and Results-In human endothelial cells, we found that eNOS activation by TNF-␣ is time dependent and requires activation of Akt, a known eNOS activator. eNOS activation was preceded by sequential activation of neutral-sphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 35 publications
6
115
0
Order By: Relevance
“…So far, TNFa-stimulated SphK activity has been shown to be critical for its antiapoptotic [16] and mitogenic [17] action, as well as for the inflammatory reaction [9,10]. The present study demonstrates that TNFa signaling via SphK1 is implicated also in the regulation of skeletal muscle differentiation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…So far, TNFa-stimulated SphK activity has been shown to be critical for its antiapoptotic [16] and mitogenic [17] action, as well as for the inflammatory reaction [9,10]. The present study demonstrates that TNFa signaling via SphK1 is implicated also in the regulation of skeletal muscle differentiation.…”
Section: Discussionsupporting
confidence: 58%
“…In view of the recognized ability of TNFa to regulate SphK [8][9][10] and the pro-myogenic role exerted by S1P and SphK in myoblasts [6,7], the effect of TNFa at low dose on SphK was then examined. Data illustrated in Fig.…”
Section: The Pro-myogenic Effect Of Tnfa Is Mediated By Sphk1mentioning
confidence: 99%
“…32 The amount of endothelial injury in the target organ and time course of local NO production after eNOS activation by Akt may play an important role for therapeutic stem cell treatment. 33 In human endothelial cells, the induction of eNOS by TNF-a has recently been described by De Palma et al 34 In contrast, a downregulation of eNOS was observed in association with high levels of TNF-a in patients with type 2 diabetes and microangiopathy. 35 Systemic L-NAME treatment and thereby …”
Section: Discussionmentioning
confidence: 85%
“…In this report, the authors showed that silencing S1P 1 and/or S1P 3 receptors by means of siRNA prevents eNOS activation by tumor necrosis factor-␣. 40 To investigate whether S1P 1 and S1P 3 receptors are involved in the Ang II-induced NO production, we tested whether the novel S1P 1 /S1P 3 receptor antagonist VPC 23019 also augments the contractile effects of Ang II in the rat carotid artery, as seen for DMS and L-NNA. Indeed, VPC 23019, one of the few available S1P receptor antagonists, induced a significant increase in E max and a small, although not significant, leftward shift of the concentration-response curve for Ang II.…”
Section: Expression Of S1p Receptor and Sphingosine Kinase Subtypes Imentioning
confidence: 99%